Random inbreeding, isonymy, and population isolates in Argentina - Dipierri, Jose Edgardo (2014)
Population isolates are an important tool in identi-fying and mapping genes of Mendelian diseases and complextraits. The geographical identification of isolates represents apriority from a genetic and health care standpoint. The pur-pose of this study is to analyze the spatial distribution ofconsanguinity by random isonymy (FST)inArgentinaanditsrelationship with the isolates previously identified in thecountry.FSTwas estimated from the surname distribution of22.6 million electors registered for the year 2001 in the 24provinces, 5 geographical regions, and 510 departments of thecountry. Statistically significant spatial clustering ofFSTwasdetermined using the SaTScan V5.1 software.FSTexhibited amarked regional and departamental variation, showing thehighest values towards the North and West of Argentina.The clusters of high consanguinity by random isonymyfollowed the same distribution. Recognized Argentinean ge-netic isolates are mainly localized at the north of the country,in clusters of high inbreeding. Given the availability of listingsof surnames in high-capacity storage devices for differentcountries, estimatingFSTfrom them can provide informationon inbreeding for all levels of administrative subdivisions, tobe used as a demographic variable for the identification ofisolates within the country for public health purposes.